ArcAid Interactive Archery Assistant - Jeroen Vervaeke; Jente Ameye; Sievert van Esch; Jelle Saldien; Steven Verstockt (EAI Endorsed Transactions on Serious Games, 2015)
This paper describes the design process of a bow aiming system, called ArcAid, which is an interactive archery assistant. The main goal of ArcAid is to introduce a way for beginner Robin Hoods to learn the art of archery to its fullest. In order to achieve this goal, our smartphone-based design focuses on a fun and interactive learning process that gives constant feedback to the user on how to hit a certain goal. A SPIKE high- end laser sensor is used for the distance measurement and the smartphone’s accelerometer is used to define the angle of inclination. To measure the force on the arrow and the displacement of the string, a flex sensor is attached upon one of the arcs of the bow. All sensor data is processed in an Arduino Nano microprocessor and feedback to the user is given by a dedicated smartphone app. In this paper, we mainly focus on the construction, mechanics and electronics of the ArcAid bow and on the design of the mobile app, which is the game controller. Furthermore, we briefly discuss some future development ideas.